The Influence of Work-Life Balance and Work Environment on Employee Performance with Work Stress as Moderation at PT. Cakrawala Andalas Television (ANTV) - Rachmayanti; Susanti Widhiastuti (Yayasan Amerta Insan Unggul, 2024)
This research aims to analyze the influence of work-life balance and work environment on employee performance with work stress as a moderating variable at PT Cakrawala Andalas Television (ANTV). Data was obtained through employee surveys and analyzed using partial tests and Moderated Regression Analysis (MRA). The research results show that work-life balance has a positive and significant effect on employee performance, indicating that balance between work and personal life increases productivity. The work environment also has a significant influence, highlighting the importance of creating a conducive work atmosphere. Job stress was found to have a direct influence on employee performance and acts as a moderator that strengthens the relationship between work-life balance and performance. The interaction between the work environment and work stress also has a positive impact on performance. These findings highlight the importance of stress management, work environment development, and strategic work-life balance programs to support employee performance on an ongoing basis. This research provides a practical contribution for companies in designing policies to optimize human resources.